Echogenic material in the fetal gallbladder: prevalence, sonographic spectrum, and perinatal outcome in an unselected third-trimester population. (2nd April 2020) - Sepulveda, Waldo; Wong, Amy E.
Abstract: Objective: To determine the prevalence, sonographic spectrum, and clinical significance of echogenic material in the fetal gallbladder in our population. Methods: Sonographic visualization of the fetal gallbladder was attempted in 3894 consecutive third-trimester pregnancies (4026 fetuses). Gallbladder content was classified as clear (anechoic), containing echogenic material that was either diffuse (sludge), or presenting as a single focus or multiple foci (gallstone(s)). Information on the clinical course was obtained by reviewing the medical records or contacting the provider or the parents themselves. Results: During the three and a half-year study period from July 2014 to December 2017, 19 fetuses were identified as having echogenic material in the gallbladder (prevalence 1/211, 0.47%). Among them, echogenic biliary sludge was found in eight fetuses (42%); all eight were asymptomatic and a normal gallbladder was documented postnatally in four of them. Single ( n  = 3) or multiple ( n  = 8) echogenic foci were found in 58% of cases, which was associated with a good prognosis and subsequent resolution between 1 and 10 months of life in all cases. Conclusions: The prevalence of echogenic material in the fetal gallbladder in our population was similar to that previously reported in the literature. The prognosis appears to be favorable, with resolution and without subsequent postnatal hepatic or gastrointestinal complications in all cases.